The association between Helicobacter pylori seropositivity and low birthweight in a Sudanese maternity hospital. Issue 2 (27th August 2018) - Mustafa, Ahmed; Bilal, Naser E.; Abass, Awad‐Elkareem; Elhassan, Elhassan M.; Adam, Ishag
Abstract: Objective: To investigate the association between Helicobacter pylori seropositivity and low birthweight (LBW). Methods: The present case–control study was conducted at a Sudanese maternity hospital from September 1 to December 30, 2015. Patients who delivered single neonates with LBW (>500 g but <2500 g) and the subsequent singleton delivery with birthweight of 2500–4000 g were included. A questionnaire was used to collect medical and obstetric data. The presence of malarial parasites in peripheral, placental, and umbilical cord samples was investigated using blood films. The presence of H. pylori immunoglobulin G (IgG) in maternal and umbilical cord serum samples was determined by enzyme‐linked immunosorbent assay. Results: The study included 87 patients in each of the LBW and control groups. Maternal serum tested positive for H. pylori IgG among 66 (75.9%) and 48 (55.2%) patients in the LBW and control groups ( P =0.006); no malarial parasites were observed. Similarly, umbilical cord serum tested positive for H. pylori IgG among 66 (75.9%) and 34 (39.1%) patients in the LBW and control groups ( P <0.001). Maternal H. pylori IgG seropositivity (OR 3.2, 95% CI 1.4–7.2; P =0.003) and umbilical cord H. pylori IgG seropositivity (OR 2.4, 95% confidence interval 2.1–10.2; P <0.001) were significantly associated with LBW. Conclusion: Seropositivity for H. pylori IgG was associated with LBW. Abstract : The presence of Helicobacter pylori immunoglobulin G in maternal and umbilical cord serum samples was associated with low birthweight in a Sudanese maternity hospital.